BENTUK PENYELESAIAN HUKUM BERKAITAN DENGAN PENCANTUMAN EXONERATION CLAUSE DAN KLAUSULA BAKU YANG DILARANG UNDANG-UNDANG PERLINDUNGAN KONSUMEN - FERNINDA PARAMITA (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT Legal protection of customers who conduct transactions E-Banking ATM particular is less fully met. This can be demonstrated by various problems tends to be detrimental to the client. Legal protection of customers who conduct transactions E-Banking is not enough with the legislation existing customers namely the Consumer Protection Act or the Banking Act for electronic banking in itself is spacious enough access so that protection is not entirely because of the Act. Whatever form of protection that can be given is protection for customers in the agreement that can be given is protection for customers in the publishing agreement and the use of ATM cards and customer protection at the time of resolution.The existence of different circumstances between the bank as business people and customers were still visible as the strong and weak. Evidenced by the standard agreement containing standard clauses in which motivation economic need load calculations normally be met by accepting the terms of the standard provided the offender, so that actors accept or reject a potent weapon for the bank as businesses. Customers do not give a chance to negotiate the agreements that have been made because of this, customers would sign the agreement or accept the agreement document.The responsibility of the bank as businesses related to the E-Banking is not all enforced, condemnation of information describing all rules are made to prevent irresponsible use have not been fully met. When in fact the bank will be responsible only an issue if the problem was accommodated and can be seen with the systems and processes that have been established. Although there are laws remain exoneration clause but there is a habit of the banks, who as a strong position. Keywords: Clause Baku, Banking Law, E-Banking, ATM